FIRM PERFORMANCE FACTORS AND EFFICIENCY OF INDONESIAN PALM OIL COMPANIES - Arif Imam Suroso; Hansen Tandra; Mukhamad Najib; Yusman Syaukat (School of Business, Bogor Agricultural University (SB-IPB), 2020)
The palm oil industry is one of the agricultural, industrial sectors with a strategic role in the national economy, especially in Indonesia. Although this industry has a high contribution in Indonesia, the oil palm plantation companies have not shown satisfactory performance. Internal firm conditions and macroeconomic variables may influence the performance of oil palm plantation companies. Therefore, this study aims to investigate the firm performance determinants and efficiency of oil palm companies in Indonesia. The samples in this research are 12 oil palm companies listed on the Indonesian Stock Exchange (BEI) for the 2014-2019 periods. The panel regression analysis and the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) are applied in this study. The first result in the panel regression shows that the firm size, exchange rate, and world CPO price affect ROA as the operational performance. Moreover, liquidity, leverage, and inflation do not affect ROA as operational performance. The second result in panel regression shows that inflation, exchange rate, and CPO World Price affect PER as the market performance. However, market performance is not affected by liquidity, leverage, and firm size. The efficiency analysis shows that the firm ranking tends to fluctuate in the observation period. This analysis defines that the oil palm plantation companies in Indonesia, on average, have a similar performance. Keywords: palm oil, firm performance, efficiency, internal conditions, macroeconomics